Selective extraction and detection of β-agonists in swine urine for monitoring illegal use in livestock breeding. (30th May 2020) - Yuan, Yanan; Nie, Hailiang; Yin, Junfa; Han, Yehong; Lv, Yunkai; Yan, Hongyuan
Highlights: A new molecular imprinting graphene nanocomposite (PIL-MIP/GO) was synthesized. PIL-MIP/GO has fast mass transfer, rich adsorption mechanism, and high selectivity. A HPLC-UV method for β-agonists was designed based on PIL-MIP/GO as PT-SPE sorbent. The method was successfully applied to detect β-agonist in swine urine. The analytical method was sensitive, selective, accurate, nonfatal, and economical. Abstract: The illegal use of β-agonists often endangers animal-derived food safety. In this study, a selective detection method for β-agonists in swine urine was established via the combination of polymeric ionic liquid-molecularly imprinted graphene oxide-miniaturized pipette tip solid-phase extraction and high-performance liquid chromatography. It is worth noting that this method relied mainly on the designed adsorbent, which presented a rich adsorption mechanism, fast mass transfer rate, and high selectivity, and was successfully utilized in the selective extraction of β-agonists from swine urine samples. The proposed method has low LOD (0.20–0.56 ng/mL), high recovery (94.9–107.9%), and high reusability (4 times, 91.9–108.8%), which indicates its high potential as a selective, sensitive, accurate, and nonfatal method for monitoring the illegal use of β-agonists in the livestock breeding stage.